Schizophrenia: duty of medical practitioner to disclose information to employer and its implication to the employee / Mohd Nezam Desa, Saharuddin Mohd Yasin, Tengku Azlan Tengku Abdullah - Desa, Mohd Nezam; Mohd Yasin, Saharuddin; Tengku Abdullah, Tengku Azlan (2012)
This research paper is conducted in order to study the dilemma faced by medical practitioner who has to disclose information on the condition of schizophrenia patients to the patient's employers of his condition. Some of these schizophrenia patients involved in job scopes that need their full attention and care, which could lead to a dangerous situation involving other employees, the employer himself as well clients of the company. Due to this, the medical practitioner is trapped between his duty of confidentiality to patient and duty to disclosure information on employee's condition to the employer. The first chapter will be the introduction on the research paper which includes objective of study and methodology to be used. The second chapter will discuss the scientific causes of schizophrenia which includes genetic and environmental causes, signs and symptoms of the disease, and effects of the chronic illness which brings detrimental effects on to the patient. The third chapter will then proceed to highlight definition of patient's confidentiality and how medical practitioner is bound under the law to protect their patients confidentiality. This chapter will also show how the disclosure of the employee's condition has always been an issue either to the employee or the medical practitioner. There are implications to the employee and the employer that have to be considered by medical practitioner before disclosure of the employee's condition can ever be made. Legally, this chapter will show the stand of the medical practitioner and whether he is authorized under the law, in any circumstances, to disclose such information to the employer. In chapter four, it will be looking at the current legal position in Malaysia as compared to other countries with regards to the disclosure of information by medical practitioner. This chapter will identify the loopholes in the current legal standing of disclosure of patient's information by medical practitioner in Malaysia against what is currently being practiced in other countries such as USA Australia, and Canada. The last chapter will review of possible options that can be proposed to be introduce to improve and strengthen the existing rules and medical procedures in the country with regards to disclosure of confidential information on patients with schizophrenia.